2017
DOI: 10.1097/md.0000000000006171
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus-negative plasmablastic lymphoma

Abstract: Rationale:Plasmablastic lymphoma (PBL) is a rare subtype of human immunodeficiency virus (HIV)-related non-Hodgkin's lymphoma that predominantly manifests in the oral cavity.Patient concerns:Three cases of HIV-negative PBL were reported.Diagnoses:HIV-negative PBLInterventions:The patient had undergone chemotherapy.Outcomes:Clinical outcomes were very poor in Cases 1 and 3; Case 2, whose diagnosis suggested no bone marrow involvement, is still alive.Lessons subsections:These cases served to broaden the reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 64 publications
(10 reference statements)
0
24
0
Order By: Relevance
“…However, PBL in HIV-negative patients have now been identified. 5 , 6 Although the exact incidence of PBL is unknown, it accounts for about 2% to 3% of all AIDS-related lymphomas. 1 , 2 , 7 Furthermore, HIV-positive patients are generally diagnosed at an earlier age with PBL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PBL in HIV-negative patients have now been identified. 5 , 6 Although the exact incidence of PBL is unknown, it accounts for about 2% to 3% of all AIDS-related lymphomas. 1 , 2 , 7 Furthermore, HIV-positive patients are generally diagnosed at an earlier age with PBL.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 10 , 11 While some studies have reported worse prognosis in HIV-negative patients that are immunosuppressed, others have reported no significant difference in the overall survival when compared with HIV-positive patients. 7 , 10 , 16 According to Lin and colleagues, 5 features associated with better survival include the use of antiretroviral therapy in HIV-positive patients and autologous stem cell transplantation. In contrast, features that are associated with poor outcome include late stage of the Ann Arbor classification system, patients who test negative for EBV and cases not responsive to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PBL has been commonly described within the oral cavity, rarely in the extraoral sites such as the nose and paranasal sinuses, gastrointestinal tract, skin and soft tissue, and lymph nodes [ 3 ]. Although the incidence is remarkably higher in the people living with HIV/AIDS (PLHA) population, PBL has also been described in immunocompetent individuals [ 5 ]. HIV-associated PBL is usually seen with individuals whose CD4 count is around 200 cells/mm 3 , mean duration of the disease is eight years, and average viral load is over 2,50,000 copies/ml [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in our case, bone marrow involvement is rare. [10][11][12][13] EB virus infection is present in 74% of the cases, and there is no standard chemotherapy regimen currently accepted for PBL. [5,9,14] Although in patients with extranodal involvement the median survival is <1 year, our patient is in remission and is followed up by the hematology clinic for 2 years without disease recurrence.…”
Section: Discussionmentioning
confidence: 99%